Pengembangan Desain Perencanaan Sistem Informasi Geografis sebagai Alternatif Pembelajaran dalam Keperawatan Kesehatan Komunitas - Nur Setiawati Dewi; Artika Nurrahima; Panji Wisnu Wirawan (Holistic Nursing and Health Science, 2019)
Introduction: The learning process of nursing students faced complexity problems, particularly in community health nursing course. There is no latest information technology application that addresses are impacted to the educational problems of undergraduate and professional nursing program. An unclearly visualization of the data assessment of community nursing care provide distresses for lecturer and nursing student. Geographic Information Systems (GIS) provide a detail visualization that related to health problems in the community. This study aims to provide a visualization about the development of  GIS that may become an alternative learning for nursing students.Methods: This article describes the part of action research process. Five nursing students and two lecturers of community health nursing were recruited. The data collection was conducted by interview and observation for data assessment in the first step of development of GIS application.Results: There were four steps of making of GIS application, which is divided into four steps, including need analyzing, application design planning, the diagram of data flow, and application description.Conclusion: The GIS has benefit for learning process, some policies are necessary to mediate the development and application of GIS for nursing students in community health nursing course.